TEORI-TEORI KEBENARAN DALAM FILSAFAT (URGENSI DAN SIGNIFIKASINYA DALAM UPAYA PEMBERANTASAN HOAXS) - Abdul Aziz Faradi (Kontemplasi: Jurnal Ilmu-Ilmu Ushuluddin, 2019)
This article reveals the theories of truth in philosophy and the possibility of its application amid the spread of hoax and false news that is increasingly widespread in Indonesian society. The discussion starts with a socio-political background that triggers the loss of critical public reason that can no longer sort out false facts and news. Furthermore, the discussion focuses on the perspectives of truth and theories of truth that emerged and developed in the philosophical tradition. At the last point, this article ends with the possibility of applying the theories of truth in society, especially in the internet and social media. Keywords: Theories of truth, correspondence, coherence, pragmatism, performance and consensus